Swampland Conjectures Compatibility and Technical Refinements in the Expanded Quantum String Theory with Gluonic Plasma (EQST-GP) Model - Ali, Ahmed (Annals of Mathematics and Physics, 2025)
This comprehensive work presents detailed mathematical formulations and technical refinements addressing critical theoretical challenges in the Expanded Quantum String Theory with Gluonic Plasma (EQST-GP) framework. We provide complete derivations for the negative energy density mechanism, Majorana gluon dark matter properties, and rigorous compatibility analysis with Swampland Conjectures. The enhanced model incorporates moduli stabilization with physically motivated uplifting potentials, refined gravitational wave predictions, and precise numerical verifications using symbolic computation. All derivations maintain mathematical rigor while ensuring phenomenological consistency with cosmological observations and experimental constraints. We explicitly address theoretical concerns regarding extreme parameter values, effective field theory validity, and provide transparent self-citation disclosure.